(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
With the advent of the world wide web, many scientists and researchers of the information society have begun to explain historical developments in terms of communication rather than industrial or agricultural progress. Beginning in the 20th and 30th centuries, a number of scholars predicted the collapse of «industrial civilization» and the rise of an «information and service society», with «information manufacturing» becoming the most important national product. Various systems based on microprocessor technology, computer networks, information technology, telecommunications, the Internet provide the flow of information that is the material and technological base of the information society. The vision of an information society is one in which people are unified and computerized and information activities are focused on the processing of information, while material production and energy production are automated, and information technology has a global character, covering all spheres of human activity.